2006
DOI: 10.1001/archopht.124.3.328
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Electroretinogram in Adults and Children With Myopia

Abstract: Objective: To determine the correlation between multifocal electroretinogram (mfERG) parameters and the severity of myopia in adults and children. Design: Observational study. Methods: Multifocal electroretinograms were recorded using the VERIS system from randomly selected eyes of 104 children and 31 adults with various degrees of myopia. Dawson, Trick, and Litzkow fiber electrodes were used and the pupil was dilated with 1% tropicamide. Subjective refraction was performed under cycloplegia and axial length m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 19 publications
2
53
1
Order By: Relevance
“…2,8,9,18,19 Researchers have suggested that the reduced ERG amplitude could result from an increase in the subretinal space, 20 reduced image size, decreased retinal illumination, and the reduced retinal cell density 9,21 in the elongated eyeball. However, none of these factors could explain the findings in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,8,9,18,19 Researchers have suggested that the reduced ERG amplitude could result from an increase in the subretinal space, 20 reduced image size, decreased retinal illumination, and the reduced retinal cell density 9,21 in the elongated eyeball. However, none of these factors could explain the findings in children.…”
Section: Discussionmentioning
confidence: 99%
“…Application of the ERG technique has provided ample evidence to confirm that myopia results in impaired retinal function. It has been reported that myopia in adults was associated with decreased nonlinear components of ERG responses, 1 multifocal ERG (mfERG) responses, 2,3 retinal adaptation response, 4 and inner retinal function. [5][6][7] Axial length was shown to be linearly related to ERG amplitudes, 8 first-order kernel, and the first slice of second-order kernel of mfERG responses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding could be partially explained mechanistically by a change in the ocular structure due to increased AL in myopic eyes that determines an increased stretching of the macular area causing a coarser distribution of cones in the posterior retina [26]. Electroretinogram testing, including multifocal electroretinography, has shown decreased b-wave amplitudes with increased AL in eyes affected by nonpathological myopia, which indicates early injury of the cones [27,28,29,30]. …”
Section: Discussionmentioning
confidence: 99%
“…Multifocal ERG has been used to localize focal retinal damage occurring in numerous diseases and disorders 20,21,22,23,24,25,26,27 and has been proven to be a reliable diagnostic tool in clinical settings. Mulifocal ERG can measure the function of the outer retina as well as the inner retina.…”
Section: Introductionmentioning
confidence: 99%